2021
DOI: 10.4236/ojn.2021.119063
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress among Nursing Students in a Private University at Puerto Rico, and Its Association with Their Academic Performance

Abstract: Background: Nursing programs have distinguished themselves for being rigorous. The college experience emerges with new challenges and demands that require adaptation in order to cope with academic stress. Situation that could lead to a non adaptive institutional environment. Objective: The purpose of this research was to determine and analyze possible repercussions of academic stress in nursing students in a Puerto Rican private university and how it affects academic performance in students. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The study by Cabanach et al [ 29 ] confirmed the structure and reliability of the Academic Stressors Scale, which has been previously validated in university contexts [ 56 , 57 , 58 , 59 , 60 ]. The scale has been adapted in Portugal [ 61 ], Peru [ 62 , 63 ], Puerto Rico [ 64 ], Mexico [ 65 ]. All these studies demonstrated and confirmed the reliability, factorial validity, and internal consistency of E-CEA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Cabanach et al [ 29 ] confirmed the structure and reliability of the Academic Stressors Scale, which has been previously validated in university contexts [ 56 , 57 , 58 , 59 , 60 ]. The scale has been adapted in Portugal [ 61 ], Peru [ 62 , 63 ], Puerto Rico [ 64 ], Mexico [ 65 ]. All these studies demonstrated and confirmed the reliability, factorial validity, and internal consistency of E-CEA.…”
Section: Literature Reviewmentioning
confidence: 99%